Combined Two-Model CFD Simulation of Trickle Bed Reactors with Head-Sump Extension: Case Study on Hydrodynamics and Biological Methanation - Markthaler, Simon; Plankenbühler, Thomas; Miederer, Jonas; Kolb, Sebastian; Herkendell, Katharina; Karl, Jürgen (Industrial & Engineering Chemistry Research, 2022)
Trickle bed reactors are one of the world’s most employed technologies for multiphase processing, and they have been scrutinized for decades. However, accurate prediction and scale-up of trickle bed reactors are still challenging owing to complex interactions of multiphase flow, interfacial mass transfer, and reaction kinetics. The present computational model provides an insight into process phenomena on the basis of Eulerian–Eulerian methodology. It captures all parts of a trickle bed reactor─packing, head, and sump─which enables simulation of co- and countercurrent flow, gas or liquid recycle, and arbitrary retention time. Applying this model, hydrodynamic simulations reveal an improved prediction of liquid holdup, liquid dispersion, and pressure drop compared to CFD models of only the trickle bed. Furthermore, the interfacial surface area is analyzed and validated on account of a literature correlation. Exemplifying the entire approach with chemical absorption and reaction, the simulation of biological methanation presents methane concentration and productivity which are of the same order of magnitude as experimental data for an operating pressure of pop = 0.1–1 MPaabs.<br